An Ergonomic Customized-Tool Handle Design for Precision Tools using Additive Manufacturing: A Case Study - Alfonso González González (Applied Sciences, 2018)
A study was carried out with 135 surgeons to obtain a surgical laparoscopic grasper handle design that adapts to the size of each surgeon’s hand, in a functionally appropriate way, and has the sufficient ergonomics to avoid generating the problems detected nowadays. The main conclusion of the work is the practical 3D parametric design obtained for a laparoscopic surgical graspers handle that is scalable to fit each particular surgeon's hand size. In addition, it has been possible to determine that the anthropometric measure of the surgeon's hand defined as Palm Length Measured (PLM) allows the design of the 3D parametric model of the surgical handle to be conveniently scaled. The results show that both additive manufacturing and the application of ergonomics criterion provide an efficient method for the custom design and manufacture of this type of specialised tool, with potential application in other sectors.